2007
DOI: 10.1002/hec.1206
|View full text |Cite
|
Sign up to set email alerts
|

Demand for private health insurance in Chinese urban areas

Abstract: Between 1993 and 2003, the proportion of urban residents without health insurance rose from 27 to 50%. The probability of outpatient visits in the previous 2 weeks dropped from 19.9 to 11.8% in urban areas between 1993 and 2003, and from 16.0 to 13.9% in rural areas. To improve risk-pooling and risk-sharing, private health insurance should play an important role in China's health insurance system. This paper estimates the demand for private health insurance in urban areas using contingent valuation methods. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 23 publications
(31 reference statements)
7
47
1
Order By: Relevance
“…The implication is that male respondents were more willing to pay for a health insurance cover than females. This result agrees with findings by Dror et al (2007), Ying et al (2007) and Kuwawenaruwa, Macha, and Borghi (2011) who also found that males are more willing to purchase a health insurance than the female headed households.…”
Section: Resultssupporting
confidence: 92%
“…The implication is that male respondents were more willing to pay for a health insurance cover than females. This result agrees with findings by Dror et al (2007), Ying et al (2007) and Kuwawenaruwa, Macha, and Borghi (2011) who also found that males are more willing to purchase a health insurance than the female headed households.…”
Section: Resultssupporting
confidence: 92%
“…Although the medical cost for UNINSUERD patients was huge, the economic burden may be partly relieved by commercial health insurance. The importance of commercial health insurance has been pointed out in several studies 30, 31. While the BSMI has broad coverage in China population, the third population cohort, some 420 million rural migrant workers, was completely left out of the BSMI prior to 2007 32.…”
Section: Discussionmentioning
confidence: 99%
“…We did not examine the educational levels of the enrolled patients, which may also influence the evaluation of relationship between BSMI and cardiac mortality in STEMI patients, since the educational levels of the patients may be different. Although the function of commercial health insurance has been reported in some previous studies 30, 31, we did not investigate the reimbursement funded by different non-government providers. The influence of commercial health insurance on the outcome of STEMI patients was only a preliminary estimate from our data.…”
Section: Discussionmentioning
confidence: 99%
“…The responses are used to derive the WTP, which reflects the value of the non-market good perceived by the respondent. The CV method has wide application in studying the value of public goods (Mitchell & Carson, 1989), risk (Arana & Leon, 2002), disease treatment and health Downloaded by [University of Kent] at 03:17 03 December 2014 (Gyrd-Hansen, 2003;Nocera, Bonato, & Telser, 2002), health care (Luchini, Protiere, & Moatti, 2003;Pavlova, Groot, & van Merode, 2004), and health insurance (Asgary, Willis, Taghvaei, & Rafeian, 2004;Ying et al, 2007). In this study we apply the method to measure the value of HCBS to low-income seniors, an application which has never been considered previously.…”
Section: Introductionmentioning
confidence: 96%